The Privileges of Men over Women in Family Matters A Comparative Jurisprudential Study - Ali, Asma'a Mohammed (Journal of Islamic Sciences, 2023)
This dissertation aims at collecting the jurisprudence laws in which men are privileged over women in family matters، It is divided into four sections، First، Men are privileged over women in their guardianship of marriage. Unlike women، men are permissible to marry without the consent of a guardian. They are also allowed to marry Christian or Jewish women (People of the Book). Polygamy (maximum of four wives) is the right of a man. Paying dowry and life expenses are paid by men for women in addition to keeping marriage guardianship and divorce. This section is devoted to Zihar as it is the right of a man، The researcher has compared among the four main Schools of Thought in Islam، namely ، Hanafis، Malikis، Shafiayas and Hanbalis. In addition to the Al-Dhahiri School of Thought whenever possible، Finally، the conclusion summarizes the findings of the study and gives some recommendations for Muslims and future researchers. The dissertation ends with the list of related references.